Expansion and differentiation of IgM+ B cells in the rainbow trout peritoneal cavity in response to different antigens. (May 2017) - Castro, Rosario; Abós, Beatriz; González, Lucia; Granja, Aitor G.; Tafalla, Carolina
Abstract: To date, intraperitoneal (i.p.) injection seems to be the most effective vaccination route in aquaculture, as many i.p. administered fish vaccines are capable of conferring strong and long-lasting immune responses. Despite this, how peritoneal leukocytes are regulated upon antigen encounter has only been scarcely studied in fish. Although, in the past, myeloid cells were thought to be the main responders to peritoneal inflammation, a recent study revealed that IgM + B cells are one of the main cell types in the teleost peritoneal cavity in response to pathogenic bacteria. Thus, in the current work, we have focused on establishing how IgM + B cells are recruited into the peritoneum in rainbow trout ( Oncorhynchus mykiss ) comparing different antigens: Escherichia coli as a bacterial model, E. coli -derived lipopolysaccharide (LPS) or viral hemorrhagic septicemia virus (VHSV). In addition to studying their capacity to dominate the peritoneal cavity, we have established how these IgM + B cells are regulated in response to the different antigens, determining their levels of IgM secretion, surface MHC II expression, cell size and phagocytic abilities. Our results reveal that IgM + B cells are one of the main cell types amplified in the peritoneum in response to either bacterial or viral antigens and that these immunogenic stimulations provoke a differentiation of some of these cells towards plasmablasts/plasma cells whereas others seem to be implicated in antigen presentation. These findings contribute to a better understanding of the immune processes that regulate peritoneal inflammation in teleost fish. Highlights: The percentage of trout peritoneal IgM + B cells significantly increases after local stimulation. Some of these IgM + B cells differentiate locally to plasmablasts/plasma cells. This differentiation only takes place when complete microorganisms are injected. IgM + B cells are the main cells phagocytosing particulate antigens in the peritoneal cavity.